Konstruksi Pemikiran Pendidikan Islam Nurcholish Madjid (Tinjauan Cabang Filsafat Pendidikan) - Prayogi, Rayinda Dwi, Dr. M. Abdul Fattah Santoso, M.Ag (2016)
Nurcholish Madjid is a figure of Islamic educational reform in Indonesia. He was a scholar who had suggested the idea, concept and Islamic thought in an effort to look to the future of the Indonesian nation. Talking about Islamic education will never finish. The most basic problem in the Islamic education is the lack of to appreciation philosophical ideas for the implementation of Islamic education. So, it is oriented to those who are not idealistic or pragmatic, the inability of students to face the challenges of life, and forming the wrong paradigm that Islamic education as only a factory of workers. Therefore the purpose of this study is to explore a framework of Nurcholish Madjid's thought about Islamic education in the perspective of branches of the philosophy of education and its relevance to the present condition of Islamic education, that can be served as guidelines for the practical implementation of Islamic education giving benefit to both the coaching new attitude of critical life and new behavior patterns as well as to face the new age. This research is qualitative. The qualitative approach emphasizes the analysis on the descriptive data form of written or spoken words of people and observed behavior. This study includes in the category of literature study (library research) which collects data and information with the help of the library literature, such as books, encyclopedias, biographies and many others. The data collected are analyzed using descriptive analysis method which consists of three main activities, namely , data reduction , data presentation and conclusion with dig deepest meanings systematically and then search for coherence, comparison and relevance base on the philosophical approach. This study shows that the construction of the Islamic educational thought of Nurcholish Madjid is stressed to the total growth of learners, both in terms of his understanding of religious rites and formalities also true life aim (intrinsic), ie closeness or "taqarrub" to God and kindness to others (morality noble). Then, the ability of realizing of Muslim personality, which is reflected Islamic teachings carried on in accordance with educational strata levels, from primary school, tsanawiyah and aliyah. Each level has continuity properties using learning methodology, the problem-solving methods, contemplation, and refraction. The benefits of education are to realize the people who have the attitude of divinity in peace and togetherness. Thus the construction of such thoughts can reap relevant concepts to be used as a reference for efforts to resolve the problems of Islamic education today.